2015
DOI: 10.7196/samj.7799
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of fingerstick blood collection for point-of-care HIV-1 viral load monitoring in South Africa

Abstract: Background. Viral load (VL) quantification is an important tool in determining newly developed drug resistance or problems with adherence to antiretroviral therapy (ART) in HIV-positive patients. VL monitoring is becoming the standard of care in many resource-limited settings. Testing in resource-limited settings may require sampling by fingerstick because of general shortages of skilled phlebotomists and the expense of venepuncture supplies and problems with their distribution. Objective. To assess the feasib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Study staff observed blood collection and documented adherence of the counselors to standard practice (Maiers et al, 2015). After blood collection, a photograph was taken of the capillary tubes and the participant’s fingertips and the participant was again asked about their preference for blood collection methods.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Study staff observed blood collection and documented adherence of the counselors to standard practice (Maiers et al, 2015). After blood collection, a photograph was taken of the capillary tubes and the participant’s fingertips and the participant was again asked about their preference for blood collection methods.…”
Section: Methodsmentioning
confidence: 99%
“…In collaboration with Quidel Corporation (USA), the Northwestern Global Health Foundation (USA) is developing a point-of-care test that will require up to 200 μL (with a target blood volume of 165 μL) of capillary blood to reach a lower limit of detection of 1 000 copies/mL. Prior studies conducted in urban clinics in South Africa have demonstrated the feasibility of collecting 95 and 150 μL of capillary blood from study participants (Gous et al, 2013, Maiers et al, 2015). Little is known about the feasibility of collecting capillary blood from patients in rural areas, where they may be more likely to be engaged in subsistence farming, fishing, mining, and other labor-intensive activities.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the development of several POC viral load technologies over the last decade (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24), there is a shortage of commercially available tests. In this study, we evaluated the performance of the POC Cepheid Xpert HIV-1 viral load test in rural communities in Botswana in order to provide additional data to policy makers regarding the use of this assay in decentralized HIV treatment programs.…”
mentioning
confidence: 99%
“…However, the volume of blood that can be consistently obtained is limited compared to venipuncture. We recently reported that it is feasible to collect 150 μl of whole blood from a fingerstick [42], from which we estimate that 50 μl of plasma can be reliably collected even if the hematocrit is as high as 55%. Based upon the LOD of the HCV Quant Assay established by testing 200 μl plasma, the LOD from 50 μl plasma would be estimated to be 120 IU/ml, i.e.…”
Section: Discussionmentioning
confidence: 99%